TATA KELOLA ADMINISTRASI BIDANG KEPEGAWAIAN DALAM MENINGKATKAN EFEKTIFITAS KERJA TENAGA KEPENDIDIKAN DAN GURU DI PESANTREN MODERN AL-ZAHRAH - Sadikin; Darmadi; Nazar, M. (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
This study examines the administrative governance of personnel in improving the effectiveness of the work of education personnel and teachers at the Al-Zahrah Modern Islamic Boarding School. The purpose of this study is to determine, explain, and analyze the implementation of administrative governance in the field of personnel at the Al-Zahrah Modern Islamic Boarding School. This type of research uses a qualitative method, the primary data source is obtained from the object of research, namely the Al-Zahrah Modern Islamic Boarding School. Data analysis uses triangulation. The results of the study indicate that: the implementation of administrative governance in the field of personnel has accessibility and linearity with the foundation's big data, the data will be used to improve performance with equal evaluative steps in empowering and utilizing education personnel and teachers who are employees of the Al-Zahrah Modern Islamic Boarding School, the challenges and obstacles are in the partialization of administration towards teachers who are seconded from related agencies, while the indicator of work effectiveness has a time duration instrument that has been systematically patterned as a target for achieving performance effectiveness based on a long-term deadline, namely short, medium and long duration.